A review of the application of hydrated salt phase change materials in building temperature control. (15th December 2022) - Chen, Zhibo; Zhang, Xuelai; Ji, Jun; Lv, Yuyun
Abstract: Energy depletion and global warming pose challenges for building temperature control, and developing new building temperature control technologies is an effective solution. The phase change temperature control technology of integrating phase change materials (PCMs) in buildings is booming, but the use of hydrated salt PCMs as temperature control materials in buildings still faces difficulties. Unfavorable factors such as supercooling, phase separation, and corrosiveness will limit the further development of hydrated salts. The content of this review mainly includes three aspects. Firstly, the different methods to effectively improve the properties of hydrated salts are analyzed, focusing on supercooling and phase separation. Secondly, the different encapsulation methods of hydrated salts are discussed, focusing on the analysis of the causes of hydrated salt leakage. Thirdly, the application researches of hydrated salts in building materials, building envelopes and air-conditioning systems are introduced. The results of these studies indicate that by optimizing its modification and encapsulation scheme, hydrated salts will have better application prospects in the field of building temperature control. Finally, some future research directions of hydrated salts are prospected. Highlights: Different methods of modifying hydrated salts are classified and summarized. The factors affecting the encapsulation effect when encapsulating hydrated salts are discussed. The effects of different applications of hydrated salts in building temperature control are summarized.